2017
DOI: 10.21273/jashs03938-16
|View full text |Cite
|
Sign up to set email alerts
|

Soil-application of Zinc-EDTA Increases Leaf Photosynthesis of Immature ‘Wichita’ Pecan Trees

Abstract: Zinc deficiency is common in pecan (Carya illinoinensis) grown in alkaline, calcareous soils. Zinc (Zn)-deficient pecan leaves exhibit interveinal chlorosis, decreased leaf thickness, and reduced photosynthetic capacity. Low photosynthesis (Pn) contributes to restricted vegetative growth, flowering, and fruiting of Zn-deficient pecan trees. Our objectives were to measure effects of soil-applied ethylenediaminetetraacetic acid (EDTA)-chelated Zn fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
1
31
2
Order By: Relevance
“…Pecan leaf greenness and P n activity are affected by leaf tissue concentrations of N and micronutrients. Heerema et al (2017) found that zinc (Zn) application via fertiga-tion increased P n on immature pecan trees. Sherman et al (2017) observed an improvement in P n under foliar applications of manganese (Mn) on nonbearing pecan trees.…”
mentioning
confidence: 99%
“…Pecan leaf greenness and P n activity are affected by leaf tissue concentrations of N and micronutrients. Heerema et al (2017) found that zinc (Zn) application via fertiga-tion increased P n on immature pecan trees. Sherman et al (2017) observed an improvement in P n under foliar applications of manganese (Mn) on nonbearing pecan trees.…”
mentioning
confidence: 99%
“…Along with its importance for plant growth and development (Broadley et al, 2012), Zn has been noted to have a critical role in defense against reactive oxygen species (Cakmak, 2000). In pecan, Zn fertilizer application and higher leaf tissue Zn concentrations up to 14-22 mg • kg -1 (by dry weight) are associated with increasing chlorophyll content and photosynthesis rate (Heerema et al, 2017;Hu and Sparks, 1991), which would likely support the biosynthesis of antioxidants and an increase in antioxidant activity. Studies have shown that foliar or soil application of Zn improved the total phenolic content and increased the antioxidant enzyme activity in other crop species, including wheat (Triticum aestivum; Ma et al, 2017), grape (Vitis vinifera; Song et al, 2015), and pistachio (Tavallali et al, 2010).…”
Section: Treatmentmentioning
confidence: 99%
“…Zinc availability for root uptake is limited due to reactions with soil carbonates and hydroxyl groups in alkaline, calcareous soils resulting in deficiencies that commonly negatively impact an orchard's tree health, fruit production, and commercial performance (Udo et al, 1970;Walworth and Heerema, 2015;. Zinc deficiency symptoms in pecan characteristically include shortened internodes (''rosette''), severely reduced leaf area, thinner leaves, wavy leaf margins, interveinal leaf chlorosis and necrosis, and shoot terminal dieback (Alben et al, 1932;Heerema, 2013;Heerema et al, 2017;Hu and Sparks, 1991;Ojeda-Barrios et al, 2012). In immature orchards, pecan tree growth and establishment rates are negatively affected by Zn deficiency (Walworth et al, 2017) and in mature orchards, Zn deficiency reduces pistillate flower production, fruit set, individual nut weight, and percent kernel weight (Hu and Sparks, 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is a critical element that is required in large quantities for vegetative growth, shoot elongation and quality nut (Huang et al 2019). In this sense, the supply of Zn 2+ is mainly carried out via foliar and on production trees (Heerema et al 2017). Its application has been observed to modify the concentration of nutrients, yield and quality of the harvested nut (Ojeda-Barrios et al 2014); however, the behavior has been inconsistent due to the soil conditions (pH and high carbonate content) and cultivar of pecan tree used (Huang et al 2019).…”
mentioning
confidence: 99%